2020
DOI: 10.1029/2019ea000697
|View full text |Cite
|
Sign up to set email alerts
|

Forecast Skill of Minimum and Maximum Temperatures on Subseasonal‐to‐Seasonal Timescales Over South Africa

Abstract: Forecast skill of three subseasonal‐to‐seasonal models and their ensemble mean outputs are evaluated in predicting the surface minimum and maximum temperatures at subseasonal timescales over South Africa. Three skill scores (correlation of anomaly, root‐mean‐square error, and Taylor diagrams) are used to evaluate the models. It is established that the subseasonal‐to‐seasonal models considered here have skill in predicting both minimum and maximum temperatures at subseasonal timescales. The correlation of anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The week 1, week 2, week 3 and week 4 averages for December, January and February are computed and averaged to form weeks 1-4 DJF seasons. The ECMWF model is used because in our previous study, it performed better than the other S2S models in terms of skill over southern Africa (Engelbrecht et al, 2021;Phakula et al, 2020).…”
Section: S2s Model Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The week 1, week 2, week 3 and week 4 averages for December, January and February are computed and averaged to form weeks 1-4 DJF seasons. The ECMWF model is used because in our previous study, it performed better than the other S2S models in terms of skill over southern Africa (Engelbrecht et al, 2021;Phakula et al, 2020).…”
Section: S2s Model Datamentioning
confidence: 99%
“…This study seeks to determine the probabilistic forecast skill level of statistically downscaled European Centre for Medium-Range Weather Forecasts (ECMWF) S2S forecasts in predicting maximum and minimum temperatures for weeks 1-4 lead times during 20-year December-January-February (DJF) seasons over South Africa. In our previous work, we tested the deterministic skill of S2S forecasts in predicting surface temperature over South Africa, without any downscaling (Phakula et al, 2020). Therefore, in this study, the focus is to determine if statistical downscaling of model forecasts improves skill or not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skill of the ECMWF, UKMO, and Centre National de Recherches Meteorologiques (CNRM; Voldoire et al, 2013) S2S project models and their MME was investigated in predicting minimum and maximum temperatures for days 1–14 (week 1 + 2), days 11–30, and days 1–30 (full month calendar) over South Africa (Phakula et al, 2020). Higher skill was found for week 1 + 2 in predicting both minimum and maximum temperatures, with the MME outperforming the individual models.…”
Section: S2s Predictions In the Southern Hemispherementioning
confidence: 99%
“…As early as 2010, the World Weather Research Programme (WWRP) and the World Climate Research Programme (WCRP) identified the need for in-depth research on the sub-seasonal to seasonal (S2S) scale to improve the prediction of extreme weather events, such as droughts, floods, and cyclones (Brunet et al, 2010). As the research continues, researchers have repeatedly argued the value of sub-seasonal forecasting studies as a key component of completing seamless forecasts (Pegion et al, 2019;Xiang et al, 2019;Phakula et al, 2020;Vijverberg et al, 2020;Manrique-Sun e´n et al, 2020;Merryfield et al, 2020). However, this timescale is hard to forecast due to the fact that the lead time is sufficiently long that the memory of the atmospheric initial conditions is lost and it is too short a time range for the variability of the ocean to have a strong influence on the atmosphere.…”
Section: Introductionmentioning
confidence: 99%